School Operational Assistance Fund Management Strategy in Improving Quality and Achievement at SDN 020 Penajam Paser Utara - Hasniaty, Sri Kurniawati, Hasniaty; Muin, Sri Adrianti (Pascasarjana STIE Amkop Makassar, 2024)
This study aims to determine and analyze the School Operational Assistance Fund Management Strategy in Improving Quality and Achievement at SD Negeri 020 Penajam.This research was conducted at SD Negeri 020 Penajam. This type of research is descriptive research with a qualitative approach. The number of informants is 4 (four) people. Using data collection techniques in the form of interview guidelines, observation and documentation.Based on the results of research and data analysis in the previous chapter that the strategy of managing school operational funds in improving quality and achievement at SD Negeri 020 Penajam. Based on the SWOT analysis shows that the strengths possessed by SD Negeri 020 Penajam make SD Negeri 020 able to compete with other schools. This is because by optimizing the management of BOS funds to establish cooperation with educational institutions and the private sector, in addition to developing extracurricular programs that are interesting and relevant to students' interests, establishing cooperation with the surrounding community and the private sector to support financing and training.Keywords: Management strategy , BOS funds, quality and achievement